Role of Homoeopathy in Irritable Bowel Syndrome - A Narrative Review (Homoeopathy for All, 2023)
Irritable bowel syndrome (IBS)  is a functional bowel disorder  characterized by abdominal pain  or discomfort and altered bowel  habits in the absence of detectable  structural abnormalities. It is  diagnosed by using clinical criteria. Depending on the diagnostic  criteria employed, IBS affects around  11% of the population globally.  There is a female predominance in  the prevalence of IBS, 25% less IBS  diagnosed in those over 50 years  and no association between IBS and  socioeconomic status.
Keywords: abdominal; socioeconomic